Zoledronic acid enhances the efficacy of the MEK inhibitor trametinib in KRAS mutant cancers. (1st February 2019) - Dai, Xinyu; Xia, Hongwei; Zhou, Sheng; Tang, Qiulin; Bi, Feng
Abstract: KRAS mutation is the most common type of mutation in human cancers. However, the direct pharmacological inhibition of KRAS has not been clinically successful. Trametinib (GSK1120212, Tram), a newer MEK inhibitor, inhibits RAS signaling through mitogen-activated protein kinase (MAPK) cascade suppression. The effectiveness of Tram in clinical practice is limited in KRAS mutant tumors compared to that in BRAF mutant tumors. Here, we found that Tram treatment provoked feedback activation of upstream RAS, thus causing an induction of phosphorylated MEK (pMEK) and phosphorylated ERK (pERK) rebound in KRAS mutant tumors. This failure of persistent ERK inhibition led to drug resistance. Zoledronic acid (ZA), a nitrogen-containing bisphosphonate, disrupts the biological activity of RAS by inhibiting its isoprenylation. Surprisingly, ZA overcame Tram resistance, and augmented antitumor activity was observed in KRAS mutant tumors both in vitro and in vivo . Furthermore, ZA enhanced the effect of Tram partially through the mevalonate pathway. In summary, the combination of the two FDA-approved drugs Tram and ZA may represent a novel therapeutic strategy for the treatment of KRAS mutant cancers. Highlights: RAS reactivation mainly mediates the Tram induced rebound of pERK in KRAS mutant tumors. The FDA-approved inhibitor ZA synergizes with Tram against KRAS mutant tumors in vivo and in vitro.